Effects of phytoplankton diversity on resource use efficiency in a eutrophic urban river of Northern China - Ma, Mengdi; Li, Jiaxin; Lu, Aoran; Zhu, Peixun; Yin, Xuwang (Frontiers in Environmental Science, 2024)
Freshwater biodiversity has been declining in urban areas, which may threaten ecosystem functions. Although many studies have demonstrated a positive correlation between biodiversity and ecosystem functioning (BEF) in terrestrial and marine ecosystems, little is known about the BEF relationship in freshwater environments, especially in highly urbanized regions where water pollution is a major concern. Eutrophication in urban water bodies may trigger algae blooms, decreasing the evenness or functional divergence (FDiv) of phytoplankton communities, thus negatively affecting ecosystem functioning. Through an annual field investigation, we clarified the relationship between phytoplankton diversity and ecosystem functioning, represented as resource use efficiency (RUE), in an urban river in northern China. Results indicated that evenness in the phytoplankton community contributes most to driving ecosystem functioning compared to environmental factors. The relative abundance of dominant Bacillariophyta was positively correlated with the resource use efficiency of phytoplankton (RUEpp) but negatively correlated with the resource use efficiency of zooplankton (RUEzp). Both phytoplankton evenness and functional divergence were negatively linked to RUEpp but positively to RUEzp. Our findings suggest that the reduction of phytoplankton evenness and functional divergence may seriously threaten resource use efficiency (RUE), and its potential mechanism can provide a crucial reference for water quality protection and sustainable water resource utilization in the basin.